Mining extractivism in Peru and national subalternity - Azamar Alonso, Aleida (Textual, 2019)
Peru has one of the highest international production levels of copper, silver, iron, and gold, among other minerals, in Latin America, as well as of foreign investment for the development of mining projects. This is mainly due to the liberalization of the sector during the 1990s and the decrease in tax requirements, which have increased interest in investing in this industry. The objective of this article is to demonstrate that to achieve the former it has been necessary to surrender numerous land rights, which has promoted an unequal development model that, from the theoretical perspective of Harvey, tends towards usurpation and plundering in the underdeveloped nations for the appropriation of their primary assets.